Astrochronology of the late Jurassic Kimmeridge Clay (Dorset, England) and implications for Earth system processes - Huang, C; Hesselbo, S; Hinnov, L (2010)
The Late Jurassic Kimmeridge Clay Formation (KCF) is an economically important, organic-rich source rock of Kimmeridgian-Early Tithonian age. The main rock types of the KCF in Dorset, UK, include grey to black laminated shale, marl, coccolithic limestone, and dolostone, which occur with an obvious cyclicity at astronomical timescales. In this study, we examine two high-resolution borehole records (Swanworth Quarry 1 and Metherhills 1) obtained as part of a Rapid Global Geological Events (RGGE) sediment drilling project. Datasets examined were total organic carbon (TOC), and borehole wall microconductivity by Formation Microscanner (FMS). Our intent is to assess the rhythmicity of the KCF with respect to the astronomical timescale, and to discuss the results with respect to other key Late Jurassic geological processes. Power spectra of the untuned data reveal a hierarchy of cycles throughout the KCF with ∼ 167 m, ∼ 40 m, 9.1 m, 3.8 m and 1.6 m wavelengths. Tuning the ∼ 40 m cycles to the 405-kyr eccentricity cycle shows the presence of all the astronomical parameters: eccentricity, obliquity, and precession index. In particular, ∼ 100-kyr and 405-kyr eccentricity cycles are strongly expressed in both records. The 405-kyr eccentricity cycle corresponds to relative sea-level changes inferred from sequence stratigraphy. Intervals with elevated TOC are associated with strong obliquity forcing. The 405-kyr-tuned duration of the lower KCF (Kimmeridgian Stage) is 3.47 Myr, and the upper KCF (early part of the Tithonian Stage, elegans to fittoni ammonite zones) is 3.32 Myr. Two other chronologies test the consistency of this age model by tuning ∼ 8-10 m cycles to 100-kyr (short eccentricity), and ∼ 3-5 m cycles to 36-kyr (Jurassic obliquity). The 'obliquity-tuned' chronology resolves an accumulation history for the KCF with a variation that strongly resembles that of Earth's orbital eccentricity predicted for 147.2 Ma to 153.8 Ma. There is evidence for significant non-deposition (up to 1 million years) in the lowermost KCF (baylei-mutabilis zones), which would indicate a Kimmeridgian/Oxfordian boundary age of 154.8 Ma. This absolute calibration allows assignment of precise numerical ages to zonal boundaries, sequence surfaces, and polarity chrons of the lower M-sequence. © 2009 Elsevier B.V. All rights reserved.